2021
DOI: 10.1101/2021.06.06.447267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multifunctionality of belowground food webs: resource, size and spatial energy channels

Abstract: The belowground compartment of terrestrial ecosystems drives nutrient cycling, the decomposition and stabilisation of organic matter, and supports aboveground life. Belowground consumers create complex food webs that regulate functioning, ensure stability and support biodiversity both below and above ground. However, existing soil food-web reconstructions do not match recently accumulated empirical evidence and there is no comprehensive reproducible approach that accounts for the complex resource, size and spa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 139 publications
(232 reference statements)
0
10
0
Order By: Relevance
“…However, the most powerful use of this classification is to assess multifunctionality of soil consumer communities via a food-web approach. In an associated conceptual soil foodweb review (Potapov, 2021), this classification and generic predator-prey interaction patterns were used to construct 'multichannel' soil food webs. This food-web model was further combined with energy flux approaches (Barnes et al, 2014(Barnes et al, , 2018 to infer multiple ecosystem functions by consumer communities, for example litter transformation, herbivory and top-down control, and to assess rapid to slow energy channelling and spatial distribution of energy fluxes in soil food webs.…”
Section: Feeding Habits Of Soil Faunamentioning
confidence: 99%
“…However, the most powerful use of this classification is to assess multifunctionality of soil consumer communities via a food-web approach. In an associated conceptual soil foodweb review (Potapov, 2021), this classification and generic predator-prey interaction patterns were used to construct 'multichannel' soil food webs. This food-web model was further combined with energy flux approaches (Barnes et al, 2014(Barnes et al, , 2018 to infer multiple ecosystem functions by consumer communities, for example litter transformation, herbivory and top-down control, and to assess rapid to slow energy channelling and spatial distribution of energy fluxes in soil food webs.…”
Section: Feeding Habits Of Soil Faunamentioning
confidence: 99%
“…Soil communities will be characterised at each sampling site based on the list of taxonomic and functional groups with data on their abundance, individual body masses, and total biomasses (the tentative list of target groups is given in Table 1). On the one hand, a taxonomic grouping should be detailed enough to make functional inferences as well as a food web reconstruction possible (Brussaard 1998, Briones 2014, Buchkowski & Lindo 2021, Potapov 2021). On the other hand, the grouping should be generic enough to include all major taxa and regions and easy enough to allow the sorting by a general soil ecologist from a mixed community image, i.e.…”
Section: Animal Identificationmentioning
confidence: 99%
“…We will also compare soil animal communities inside and outside of the protected areas worldwide to evaluate the effect of current conservation practices on soil animal communities. To analyse the animal data, we will use different approaches, such as path analysis (Eisenhauer et al 2015), geospatial modelling (van den Hoogen et al 94 (1) 2022 2021), food-web reconstruction and modelling (de Vries et al 2013, Potapov 2021, and energy flux approaches (Barnes et al 2018, Jochum et al 2021. We also plan to link collected animal data with multiple functional traits to assess global variation in the functional diversity of soil animal communities (Pey et al 2014, Brousseau et al 2018 and work on integration of our results in suggested animal-based biogeochemical models (Chertov et al 2017, Deckmyn et al 2020, Flores et al 2021.…”
Section: Future Prospectsmentioning
confidence: 99%
See 2 more Smart Citations